Intent Classification by the Use of Automatically Generated Knowledge Graphs - Mihael Arcan; Sampritha Manjunath; Cécile Robin; Ghanshyam Verma; Devishree Pillai; Simon Sarkar; Sourav Dutta; Haytham Assem; John P. McCrae; Paul Buitelaar (Information, 2023)
Intent classification is an essential task for goal-oriented dialogue systems for automatically identifying customers’ goals. Although intent classification performs well in general settings, domain-specific user goals can still present a challenge for this task. To address this challenge, we automatically generate knowledge graphs for targeted data sets to capture domain-specific knowledge and leverage embeddings trained on these knowledge graphs for the intent classification task. As existing knowledge graphs might not be suitable for a targeted domain of interest, our automatic generation of knowledge graphs can extract the semantic information of any domain, which can be incorporated within the classification process. We compare our results with state-of-the-art pre-trained sentence embeddings and our evaluation of three data sets shows improvement in the intent classification task in terms of precision.